Fascist spectacle : the aesthetics of power in Mussolini's Italy - Falasca-Zamponi, Simonetta, 1957- (Berkeley : University of California Press, 1997)
At the end of October 1922, in a whirlwind of events and unexpected circumstances, Benito Mussolini became prime minister of Italy. For the next twenty years, he dominated Italy as a cult hero and the duce of fascism and, later, founder of the empire. This richly textured cultural history traces the narrative path that accompanied the making of the fascist regime and the construction of Mussolini's power. Simonetta Falasca-Zamponi reads fascist myths, rituals, images, and speeches as texts that tell the story of fascism. Linking Mussolini's elaboration of a new style of rule to the shaping of the regime's identity, she finds that in searching for symbolic means and forms to represent its political novelty, fascism actually created its own power, its own happening, its history.
1. Mussolini's Aesthetic Politics. The Politician as Artist. From Art to Violence -- 2. Mussolini the Myth. Mussolini in the Culture of Personality. Mussolini and the Party. The Deification of Mussolini -- 3. The Politics of Symbols: From Content to Form. The Myth of Rome. The Discourse on Style -- 4. Bodily Economy: Corporativism and Consumption. Disembodying the Body. Material/Consumption. Mimetic Economy. Spectacle and Desire -- 5. War and Melodrama. The Politics of Land. The Politics of War.
Includes bibliographical references (pages 267-293) and index.
Print version record.
English.
JSTOR
Keywords: Fascism -- Italy; Italy -- Politics and government -- 1922-1945.; Fascism and culture -- Italy; Aesthetics, Italian -- 20th century; Fascisme -- Italie; Italie -- Politique et gouvernement -- 1922-1945.; Fascisme et culture -- Italie; POLITICAL SCIENCE -- Political Ideologies -- Fascism & Totalitarianism; HISTORY / Europe / General; Aesthetics, Italian; Fascism; Fascism and culture; Politics and government; Italy; Fascisme; Machtsvertoon; Theatraliteit; Italië; Fascisme -- Italie -- 1900-1945.; Fascisme et culture -- Italie; Esthétique italienne -- 1900-1945.; Italie -- Politique et gouvernement -- 1922-1945.; 1900-1999